Industrial accident - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
This case looks at the 2010 explosion of the Tesoro Corporation refinery in the United States. It shows how the resulting investigation discovered a host of health and safety violations in the company's history; it also demonstrates how ineffective enforcement of industry regulations can have far reaching consequences.